Effect of an exhaustive swim exercise on isometric peak torque and stroke paramters - Greco, C. C.; Bassan, N. M.; César, T. E. A. S.; Denadai, B. S. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
In swimming, biomechanical aspects, such as drag and the level of application of propulsive force as well as physiological aspects associated to the energy production are important for performance (Hollander et al. 1986). Some technical parameters such the stroke rate (SR) and stroke length (SL) have shown significant changes throughout competitive races (Craig et al. 1985) as well as constantspeed tests (Dekerle et al. 2005; Alberty et al. 2009; Pelarigo et al. 2011; Oliveira et al. 2012), which have been attributed to the compromised capacity to generate force to overcome drag (Craig et al. 1985). Thus, the changes in swim technique have been attributed to fatigue (i.e., the reduced capacity to produce force) (Gandevia 2001). Indeed, decrements on power, speed and SR have been demonstrated during swim exhaustive tests (Toussaint et al. 2006). Moreover, Aujouannet et al. {2006) have shown significant changes in SR and SL throughout an exhaustive test and maximal isometric force, performed in a swim bench. At similar swim conditions, lkuta et al. (2012) verified significant reduction of electromyographic activity of biceps brachii and triceps brachii muscles during the test. However, no studies have determined the relationship between changes in musce strength and the changes in swim technique in exhaustive swim tests. In front-crawl swimming, the propulsion is produced mainly by arm movements (Hollander et al. 1987). Among the main muscles utilised for propulsion are the triceps brachii and biceps brachii, which are essential during the underwater phase of the stroke (Ciarys 1983). Indeed, Figueiredo et al. (2013) have demonstrated significant changes in the amplitude (triceps brachii and biceps brachii) and frequency (triceps brachii) electromyography parameters throughout a maximal 200-m front crawl swim test. Thus, the objective of this study was to correlate the changes in the isometric peak torque (IPT) of elbow flexors (EF) and elbow extensors (EE) and the stroke parameters (i.e., SR and SL) induced by an exhaustive swim. it was hypothesised that a direct relationship might exist between the changes in swim technique and force.